2018
DOI: 10.3389/fphar.2018.01485
|View full text |Cite
|
Sign up to set email alerts
|

Single and Repeated Administration of Methylphenidate Modulates Synaptic Plasticity in Opposite Directions via Insertion of AMPA Receptors in Rat Hippocampal Neurons

Abstract: Methylphenidate (MPH) is widely used in the treatment of Attention Deficit Hyperactivity Disorder. Several lines of evidence support that MPH can modulate learning and memory processes in different ways including improvement and impairment of test performances. A relevant factor in the efficacy of treatment is whether administration is performed once or several times. In this study we demonstrate opposite effects of MPH on performance of preadolescent rats in the Morris Water Maze test. Animals treated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…However, PNE animals treated with a single oral dose of MPH show a complete recovery of LTP (PNE: 127.8 ± 1.75 n = 10.15; PNE + MPH: 151.6 ± 3.246 n = 9.14). As we have previously reported [20], a single dose of MPH increases hippocampal LTP in control no−PNE by about 50%. To determine whether the recovery of LTP by MPH was due to presynaptic or rather postsynaptic changes, we used a paired-pulse facilitation protocol that allows us to study the facilitation of synaptic response as the ratio of onset slopes of first and second evoked responses.…”
Section: Mph Restores Electrophysiological Parameters and Neuroplasti...supporting
confidence: 78%
See 2 more Smart Citations
“…However, PNE animals treated with a single oral dose of MPH show a complete recovery of LTP (PNE: 127.8 ± 1.75 n = 10.15; PNE + MPH: 151.6 ± 3.246 n = 9.14). As we have previously reported [20], a single dose of MPH increases hippocampal LTP in control no−PNE by about 50%. To determine whether the recovery of LTP by MPH was due to presynaptic or rather postsynaptic changes, we used a paired-pulse facilitation protocol that allows us to study the facilitation of synaptic response as the ratio of onset slopes of first and second evoked responses.…”
Section: Mph Restores Electrophysiological Parameters and Neuroplasti...supporting
confidence: 78%
“…We have demonstrated that, at the hippocampal CA3/CA1 synapse, MPH induces a DA-and NE-receptor-dependent increase of LTP due to the postsynaptic insertion of AMPA receptors (AMPAR) [19]. Furthermore, we have shown that MPH augments hippocampal CA3/CA1 LTP depending on alpha1 and D1/D5 receptor activation via the intracellular messenger chain involving the cAMP/PKA/PSer845 pathway [20].…”
Section: Role Of the Hippocampus In Neuroplastic Changes Related To A...mentioning
confidence: 88%
See 1 more Smart Citation
“…The authors proposed that the volumetric reductions were caused by neuronal atrophy within the subregions ( Al-Amin et al, 2018 ). Moreover, chronic methylphenidate (MPH) exposure at high doses has been shown to induce neuronal cell death in the rat hippocampus CA1 regions ( Carvallo et al, 2018 , Schmitz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies conducted in rodents have found that psychostimulants increased synaptic levels of DA and NE in several brain regions, notably the prefrontal cortex, a region robustly associated with ADHD, and the hippocampus ( Berridge and Devilbiss, 2011 , Carvallo et al, 2018 , Kuczenski and Segal, 2001 ). Changes in the hippocampus induced by psychostimulants have been implicated in the therapeutic response and as a potential side-effect ( Britton & Bethancourt, 2009 ).…”
Section: Discussionmentioning
confidence: 99%